TECHNOLOGICAL PEDAGOGICAL AND CONTENT KNOWLEDGE (TPACK) SKILLS OF PRIMARY SCHOOL TEACHER EDUCATION STUDENTS - Angkoso, Yunus Bagus; Soepriyanto, Yerry; Adi, Eka Pramono (Universitas Negeri Malang, 2024)
Technological Pedagogical Content Knowledge (TPACK) skills must be possessed by every prospective teacher, with TPACK skills possessed by prospective teachers being able to create learning by the characteristics of 21st-century human resources who have a high level of technological agility. This study aims to describe the TPACK skills of students as prospective elementary school teachers. The method used is descriptive quantitative, with data collection techniques through distributing questionnaires using a Likert scale. To determine the level of TPACK skills, level categories will be carried out, namely high, medium, and low. The subjects of this study were 61 elementary school teacher education students at the State University of Malang in their seventh semester. The results showed that the TPACK skills of prospective elementary school teachers were in the high category with a percentage of 70%. This means that students as prospective elementary school teachers already have aspects of TPACK skills. Keywords: Technological Pedagogical Content Knowledge (TPACK); Pre Service Teachers; Teaching Readiness